A redescription of Metopa species (Amphipoda, Stenothoidae) based on the type material. 2. The United States National Museum of Natural History (NMNH) - Tandberg, Anne Helene S. (Zootaxa, 2009)
This paper presents redescriptions of amphipods in the genus Metopa (Stenothoidae) in the type-collections of the United States National Museum of Natural History, Smithsonian Institution. Typeand paratype-material is used for Metopa spinicoxa and M. stelleri. The material used for M. dawsoni is from a station very close to the type locality, and identified by Barnard, who is the author of the species. We have used material from the Albatross expedition in 1906, identified by Shoemaker, for M. cristata and M. majuscula, both originally described by Gurjanova. All species are redescribed using line drawings, and comparisons with the original texts and figures.Key words: